Watesjaya Village Governance in Empowering Communities Affected by the Development of the Special Economic Area of Lido - M. Agung Gumilar Anmuma; Ida Widianingsih; Ramadhan Pancasilawan (Budapest International Research and Critics University, 2022)
This paper discusses the governance of the Watesjaya village government in empowering farmers affected by the development of the Lido SEZ. The development of the Lido SEZ not only gives hope that it will be produced but also has a direct impact on the farmers of Ciletuh Hilir village, Watesjaya village. This happens due to the conversion of agricultural land into non-agricultural land which causes the Ciletuh farming community to be powerless and need to be empowered, this is the duty and obligation of the government to re-empower these residents to remain productive. This obligation is not only the responsibility of the center or the regions, but is the responsibility and authority of the village as the executor of government at the level closest to the community. To find out how the process of implementing village government governance works, the researcher uses 4 principles of good governance as indicators that will be investigated in the Watesjaya village government. These principles are accountability, transparency, openness, and the rule of law. This paper is descriptive with a phenomenological approach and the data collection of this research includes observation, interviews, and literature study.